Reproducibility of current classifications of endometrial endometrioid glandular proliferations: further evidence supporting a simplified classification. Issue 2 (20th September 2013) - Ordi, Jaume; Bergeron, Christine; Hardisson, David; McCluggage, W. Glenn; Hollema, Harry; Felix, Ana; Soslow, Robert A; Oliva, Esther; Tavassoli, Fattaneh A; Alvarado‐Cabrero, Isabel; Wells, Michael; Nogales, Francisco F
<x xml:space="preserve">Abstract</x> Aims To compare the reproducibility of the current (2003) World Health Organization (WHO), endometrial intraepithelial neoplasia (EIN) and European Working Group (EWG) classifications of endometrial endometrioid proliferations. Methods and results Nine expert gynaecological pathologists from Europe and North America reviewed 198 endometrial biopsy/curettage specimens originally diagnosed as low‐grade lesions. All observers were asked to classify the cases by using the categories described in each scheme: six for WHO, four for EIN, and three for EWG. The results were evaluated by kappa statistics for more than two observations. The analysis was repeated using only two major categories (benign versus atypical/carcinoma). Both the WHO and EIN classifications showed poor interobserver agreement (κ = 0.337 and κ = 0.419, respectively), whereas the EWG classification showed moderate agreement (κ = 0.530). Full agreement between pathologists occurred in only 28% for the WHO classification, 39% for the EIN classification, and 59% for the EWG classification. With only two diagnostic categories, kappa values increased in all classifications, but only the EWG classification reached a substantial level of agreement (κ = 0.621); similarly, full agreement among all pathologists increased to 70% for the WHO classification, 69% for the EIN classification, and 72% for the EWG classification. Conclusions A two‐tier classification of endometrial endometrioid proliferative lesions improves reproducibility, and should be considered for the diagnosis of endometrial biopsy/curettage specimens.